Acute and delayed cytopenias following CAR T-cell therapy: an investigation of risk factors and mechanisms. Issue 8 (3rd July 2022) - Brudno, Jennifer N.; Natrakul, Danielle; Lam, Norris; Dulau-Florea, Alina; Yuan, Constance M.; Kochenderfer, James N.
Abstract: Prolonged myelosuppression after chimeric antigen receptor (CAR) T-cell therapy is common and poorly understood. A retrospective analysis of 43 patients was conducted to investigate factors contributing to CAR T-cell-related cytopenias. Thirty-five patients were evaluable for analysis of delayed cytopenias occurring after initial hematologic recovery. Time to hematologic recovery (TTHR) was defined as number of days after CAR T-cell infusion for recovery to hemoglobin ≥8.0 g/dL, platelets ≥50.0 k/µL, and neutrophil count ≥1.0 k/µL without transfusions or growth factors for 7 days. Baseline percent bone marrow (BM) malignancy involvement correlated with TTHR ( p  = .0047). Patients with grades 3–4 cytokine-release syndrome (CRS) had longer TTHR than those with grades 0–2 CRS ( p  = .0479). Patients who developed prolonged or delayed cytopenias after anti-BCMA CAR T cells had a higher percentage of BM aspirate CAR + cells at 2 months ( n  = 10; p  = .0159).